Extracting energy while reducing hydroelastic responses of VLFS using a modular raft wec-type attachment. (March 2019) - Nguyen, H.P.; Wang, C.M.; Flocard, F.; Pedroso, D.M.
Highlights: A modular raft WEC-type attachment comprising multiple independent pontoons is proposed for extracting energy while reducing hydroelastic responses of VLFS. The hybrid Finite Element-Boundary Element (FE-BE) is extended for hydroelastic analysis of VLFS with WEC-type attachment. Effects of pontoon length, PTO damping coefficient, and incident wave angle are investigated. The proposed modular attachment outperforms the rigid attachment consisting of a single wide pontoon in extracting energy and reducing deflections of VLFS in oblique waves. It is possible to have a considerable gap between pontoons without significantly compromising the effectiveness of the modular attachment. Abstract: This paper presents the use of a modular raft Wave Energy Converter (WEC)-type attachment at the fore edge of a rectangular Very Large Floating Structure (VLFS) for extracting wave energy while reducing hydroelastic responses of the VLFS under wave action. The proposed modular attachment comprises multiple independent auxiliary pontoons (i.e. modules) that are connected to the fore edge of the VLFS with hinges and linear Power Take-Off (PTO) systems. For the hydroelastic analysis, the auxiliary pontoons and the VLFS are modelled by using the Mindlin plate theory while the linear wave theory is used for modelling the fluid motion. The analysis is performed in the frequency domain using the hybrid Finite Element-Boundary Element (FE-BE) method. Parametric studies are carried out to investigate the effects of pontoon length, PTO damping coefficient, gap between auxiliary pontoons, and incident wave angle on the power capture factor as well as reductions in the hydroelastic responses of the VLFS with the modular attachment. It is found that in oblique waves, the modular attachment comprising multiple narrow pontoons outperforms the corresponding rigid attachment that consists of a single wide pontoon with respect to the power capture factor and the reduction in the deflection of the VLFS. In addition, it is possible to have a considerable gap between pontoons without significantly compromising the effectiveness of the modular attachment.